Review of Converter Circuits with Power Factor Correction - Angel Quiroga; Jhon Bayona; Helbert Espitia (Technologies, 2025)
This article reviews converter circuits with power factor correction considering issues that arise in implementing such circuits. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) procedure are employed for the review. Six topologies with power factor correction were considered including boost, buck, buck-boost, Cük, dual boost, and totem pole bridgeless. The main findings highlight various implementation alternatives for these converters, taking into account complexity, performance, control strategies, and applications. Additionally, the review identified studies based on simulation and hardware implementation. Several alternatives exist for research to improve energy conversion circuits using conventional techniques such as PI controllers or novel controllers using artificial intelligence techniques such as neural networks. Finally, it should be noted that converter circuits with power factor correction are crucial for developing various electrical and electronic devices in domestic and industrial applications.